Energy & resource development of continental margins - Yen, Teh Fu 1927-2010; Walsh, Don 1931- (Pergamon Press, 1980)
Energy & Resource Development of Continental Margins is a collection of papers that addresses issues in the development of energy technology and exploration of energy sources. The title first covers concerns in geological and geochemical explorations. Next, the selection deals with the issues in utilizing novel methods for energy resource recovery. The text also tackles environmental constraints and pollutant analysis. The last section talks about the social impact and safety of onshore and offshore activities. The book will be of great use to scientists, engineers, and technicians involved in the research, development, and implementation of energy technology.--Provided by publisher.